Tingkat Konsentrasi Belajar Anak pada Siswa Kelas IV SD melalui Brain Gym (Senam Otak) - Heni Heni; Ulvi Nurlika (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of the brain gym on the level of concentration in children's learning in fourth-grade elementary school students at SDN Cimalaka II, Cimalaka District, Sumedang Regency. The research method used is a quasi-experimental design using one group pre-test and post-test design. The results showed that the average level of learning concentration in fourth-grade elementary school students before the brain gym was done was 6.18, with a standard deviation of 1.632. Meanwhile, the intermediate level of learning concentration in fourth-grade elementary school students after brain gym is done 7.01 with a standard deviation of 1.291. Bivariate analysis showed that the average increase was 7.09, evidenced by a p-value of 0.001 <0.05. In conclusion, the brain gym affects concentration in children's learning in fourth-grade elementary school students at SDN Cimalaka II, Cimalaka District, Sumedang Regency. Keywords: Brain Gym, Learning Concentration, Elementary School Students